Gestão pública municipal de esporte no estado do Paraná: estrutura administrativa e financiamento - Santos, Luciana Letícia Sperini Rufino dos (2016)
Public policy maybe understood as a question of the State, or as a matter of State action. It is in the middle of the process of application of public services and is deliberated in the condition of social activity, it is also understood as an action of the governmentt to fulfil the demands of the population. Since the 1988 Federal Constitution, sport has secured financing for the development of its actions at various levels of government (BRAZIL, 1988). The Brazilian State is structured in federated entities, they are: the Union, the states (and the Federal District) and counties. The administration of each of these entities is autonomous, presenting an organizational structure of its own. The agencies responsible for developing public sports policies in the public sector generally belong to the model of direct execution through Secretariats and Departments or, in some cases, in the indirect model with Autarchies and Foundations (SANTOS, 2014). The first model presents more centralized characteristics, in which the link is total to the public administration. In the second one, the execution of the services occurs in a more decentralized way, performed by out sourced labor force and not being totally linked to the public power. The main point here is to analyze the relationship of the administrative structure of municipal sports agencies on the financing of sports public policies in counties of the state of Parana. In order to this happen, we identified the administrative structure of the municipal sports agencies, verified the financial resources allocated to thes estructures and finally analyzed whether there is a correlation betweem the two variables. Our sample was composed of 80 counties in the state of Paraná. The information used for the analysis was taken from the data base of the research "Analysis of the public agents of the national sports system" and from the Counties Transparency Portal. The data analysis was performed used the statistical software SPSS®. It was observed the predominance of structures that set the direct administration, specially, Sports Departments that are mostly inserted in counties with up to 20 thousand in habitants. The average value for the development of sports public policies in counties is 1.1%. The Sports Foundations presented the high est average percent ageamong administrative structures, 1.96%, followed by Secretariats (1.58%) and Departments (1.23%). The data indicat et hat there is no direct relation ship bet weenthe management structure, in relation to the amount of financial resource that eachtype of structure presents. The budget appears as a fundamental element, however, the management model seems to be more significant than the financing of the actions itself, identifying the sports manager as a central figure in the midst of conducting the two variables.